Radiation-induced Non-targeted Effect and Carcinogenesis; Implications in Clinical Radiotherapy - R Yahyapour; A Salajegheh; A Safari; P Amini; A Rezaeyan; A Amraee; M Najafi (Journal of Biomedical Physics and Engineering, 2018)
Bystander or non-targeted effect is known to be an interesting phenomenon in radiobiology. The genetic consequences of bystander effect on non-irradiated cells have shown that this phenomenon can be considered as one of the most important factors involved in secondary cancer after exposure to ionizing radiation. Every year, millions of people around the world undergo radiotherapy in order to cure different types of cancers. The most crucial aim of radiotherapy is to improve treatment efficiency by reducing early and late effects of exposure to clinical doses of radiation. Secondary cancer induction resulted from exposure to high doses of radiation during treatment can reduce the effectiveness of this modality for cancer treatment. The perception of carcinogenesis risk of bystander effects and factors involved in this phenomenon might help reduce secondary cancer incidence years after radiotherapy. Different modalities such as radiation LET, dose and dose rate, fractionation, types of tissue, gender of patients, etc. may be involved in carcinogenesis risk of bystander effects. Therefore, selecting an appropriate treatment modality may improve cost-effectiveness of radiation therapy as well as the quality of life in survived patients. In this review, we first focus on the carcinogenesis evidence of non-targeted effects in radiotherapy and then review physical and biological factors that may influence the risk of secondary cancer induced by this phenomenon.